Development of Dynamic EV Load Model for Power System Oscillatory Stability Studies - Dharmakeerthi, C.H.; Mithulananthan, N.; Atputharajah, A. (My University, 2014)
The interest on electric vehicles growing as a sustainable alternative to fossil fuel driven vehicles. Even though there are a number of grid impact studies, only a scant attention has been paid to study the impact of EV charging on system stability. Electrification of transportation brings significant load integration to the grid. This could profoundly influence stability of the grid. Hence, it is important to understand the EV charging impact on power system stability. The extant literature is largely based on conventional load characteristics rather than actual EV load behaviours, due to the unavailability of proper load models. Hence, this study develops a dynamic EV load model, considering the dynamics of the EV charger and the battery, as an essential basis for system oscillatory stability studies. Dynamic behavior of a power electronically controlled EV load is described by an eleventh order model. The preliminary results suggest that EV load can cause considerable influence on damping performance of electromechanical modes.
Keywords: Dynamic load model; Electric vehicle